The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/0102-311x00060118
|View full text |Cite
|
Sign up to set email alerts
|

Abuso digital ou prova de amor? O uso de aplicativos de controle/monitoramento nos relacionamentos afetivo-sexuais

Abstract: Na cultura digital, há um embaralhamento entre as fronteiras do público e do privado, e nos convida a sermos, ao mesmo tempo, controladores e controlados. Este artigo analisou as produções discursivas sobre controle e monitoramento do parceiro veiculadas nas ferramentas digitais ofertadas pelos sistemas Android e iOS, disponíveis nos aplicativos de telefonia móvel. Adotamos a análise do discurso crítico para o exame e interpretação das enunciações textuais de quarenta aplicativos dos sistemas Android e iOS des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
1
11
0
7
Order By: Relevance
“…In this space, new forms of violence known as cyberbullying or e-violence [ 4 ] occur, as reflected in the definition of TDV by the Centers for Disease Control and Prevention [ 8 ]. This new digital field recognises abuse, humiliation, insults, threats, control, and isolation, among others, which can be exercised in the relational framework of a teenage couple [ 9 ]. Furthermore, the types of psychological violence are predictors of future physical violence [ 10 ] and, it has been shown that psychological aggressions usually occur in the initial moments of the relationship in young couples [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this space, new forms of violence known as cyberbullying or e-violence [ 4 ] occur, as reflected in the definition of TDV by the Centers for Disease Control and Prevention [ 8 ]. This new digital field recognises abuse, humiliation, insults, threats, control, and isolation, among others, which can be exercised in the relational framework of a teenage couple [ 9 ]. Furthermore, the types of psychological violence are predictors of future physical violence [ 10 ] and, it has been shown that psychological aggressions usually occur in the initial moments of the relationship in young couples [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Para além da violência no mundo real a temos também presente nas plataformas online e em aplicativos de relacionamento, no qual o parceiro apresenta atitudes tóxicas que vão desde humilhar, insultar, divulgar conteúdo privado das parceiras, ameaçar, como também provocar isolamento e controle sobre o outro (Flach & Deslandes, 2019;. Em estudo com 1113 participantes Maftei e Dănilă (2021), confirmam que o desengajamento moral social está ligado aos altos níveis de perpetração da violência contra os parceiros e o mais grave é que cerca de 13,7% a 23% dos participantes em todos grupos analisados afirmaram que o contexto pandêmico contribuiu para aumentar a frequência dos comportamentos violentos dos parceiros.…”
Section: Revistaunclassified
“…Gender inequality is a central focus of feminist research methodology. Considerable research suggests that heterosexual IPV is gendered, with women disproportionately represented as victim/survivors and men as perpetrators (Bancroft, 2002;Fitz-Gibbon, Walklate, McCulloch, & Maher, 2018). Research suggesting symmetry between the sexes in youth IPV (e.g., Strauss, 2004;Wolfe et al, 2001) has been criticized for using methods that fail to capture the violent context, dynamics of power and control, and acts of self-defense typically present in IPV (DeKeseredy & Schwartz, 1998;Dobash & Dobash, 1995), and for failing to take into account youth experiences with IPV (Daff et al, 2018;Minayo, Assis, & Njaine, 2011).…”
Section: Southern Feminist Frameworkmentioning
confidence: 99%